2006
DOI: 10.1038/sj.ejcn.1602410
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, oxidative stress, and pulmonary function in individuals diagnosed with asthma or COPD

Abstract: Objective: The objective of this study was to investigate the association between antioxidant nutrients and markers of oxidative stress with pulmonary function in persons with chronic airflow limitation. Design: Cross-sectional study exploring the association of antioxidant nutrients and markers of oxidative stress with forced expiratory volume in the first second (FEV 1 %) and forced vital capacity (FVC%). Setting/Subjects: The study data included 218 persons with chronic airflow limitation recruited randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 29 publications
(39 reference statements)
11
97
2
Order By: Relevance
“…Our findings indicate a significant increase in both systemic oxidative stress markers (8-OHdG, MDA and AOPP) and increased antioxidant enzyme activity (GPX) in COPD patients compared with healthy control subjects, and are in similar agreement with other published data [28][29][30][31]. In contrast to our results, increased glutathione has previously been shown to be negatively correlated with lung function in patients with chronic airflow limitation [30]. We suspect that there may be an adaptive response involved in the oxidative stress-antioxidant enzyme response, and that the high level of oxidants stimulates the antioxidant enzymatic system in an effort to counteract the high burden of oxidants.…”
Section: Molecular Markerssupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings indicate a significant increase in both systemic oxidative stress markers (8-OHdG, MDA and AOPP) and increased antioxidant enzyme activity (GPX) in COPD patients compared with healthy control subjects, and are in similar agreement with other published data [28][29][30][31]. In contrast to our results, increased glutathione has previously been shown to be negatively correlated with lung function in patients with chronic airflow limitation [30]. We suspect that there may be an adaptive response involved in the oxidative stress-antioxidant enzyme response, and that the high level of oxidants stimulates the antioxidant enzymatic system in an effort to counteract the high burden of oxidants.…”
Section: Molecular Markerssupporting
confidence: 82%
“…In addition to endogenous sources of ROS (normal cellular metabolism), COPD patients are exposed to exogenous forms of free radicals from environmental pollutants and/or cigarette smoke. Our findings indicate a significant increase in both systemic oxidative stress markers (8-OHdG, MDA and AOPP) and increased antioxidant enzyme activity (GPX) in COPD patients compared with healthy control subjects, and are in similar agreement with other published data [28][29][30][31]. In contrast to our results, increased glutathione has previously been shown to be negatively correlated with lung function in patients with chronic airflow limitation [30].…”
Section: Molecular Markerscontrasting
confidence: 57%
“…Vitamin C (ascorbic acid) is a water-soluble, chain-breaking antioxidant, which scavenges aqueous superoxide radicals and has multiple antioxidant properties. Reductions in serum vitamin C concentrations were recently shown to be related to the severity of obstructive lung impairment in COPD (Ochs-Balcom, 2006). This finding supports the hypothesis that the oxidant/antioxidant imbalance is associated with chronic airflow limitation.…”
Section: Non-enzymatic Antioxidantssupporting
confidence: 79%
“…Again, antioxidant capacity in serum is reduced in asthmatics during exacerbations as compared with healthy individuals and is less reduced in subjects with stable asthma (Katsoulis et al, 2003). Very recently, oxidative stress has been shown to be increased in children with previous bronchilitis obliterans (Mallol et al, 2011) and although in this study the authors did not find correlation with lung function tests, several studies have indeed shown an inverse relationship between oxidative stress and lung function in asthmatics (Nadeem et al, 2005;Ochs-Balcom et al, 2006;Picado et al, 2001;Wood et al, 2000). Taken together these results indicate that an oxidant-antioxidant imbalance could play a crucial role in the development of asthma symptoms and in the severity of the disease.…”
Section: Diet As An Independent Factor In the Development Of Asthma Acontrasting
confidence: 55%